2020
DOI: 10.1155/2020/8875230
|View full text |Cite
|
Sign up to set email alerts
|

I/D Polymorphism Gene ACE and Risk of Preeclampsia in Women with Gestational Diabetes Mellitus

Abstract: Preeclampsia (PE) and gestational diabetes mellitus (GDM) are the most common complications of pregnancy, which result in adverse outcomes for the mother and the fetus. GDM is regarded as a separate independent risk factor for PE development, as evidenced by a higher preeclampsia rate in gestational diabetes mellitus than in the general population. The role the endothelial cell dysfunction plays is considered to be the most reasonable one in the origin of these diseases. The activity of plasma and tissue angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Some studies suggest that TNF-α, IL-6, and C-reactive protein (CRP) are independent risk factors for PE in women with GDM ( 94 , 175 , 176 ), and others suggest that in addition to the increased level of CRP, the imbalance of Interleukin-17 /Interleukin-35 may also be involved in the pathogenesis of GDM complicated with PE ( 177 ). Genetic variants are also associated with PE in women with GDM, the MIR146Ars2910164CC genotype, HNF1αgene p. I27L TT genotype, and ACE I / D polymorphism DD genotype was significantly higher in women with GDM complicated with PE ( 178 180 ). Obesity is the main influencing factor of PE in women with GDM in this paper.…”
Section: Mechanism and Predictive Markersmentioning
confidence: 99%
“…Some studies suggest that TNF-α, IL-6, and C-reactive protein (CRP) are independent risk factors for PE in women with GDM ( 94 , 175 , 176 ), and others suggest that in addition to the increased level of CRP, the imbalance of Interleukin-17 /Interleukin-35 may also be involved in the pathogenesis of GDM complicated with PE ( 177 ). Genetic variants are also associated with PE in women with GDM, the MIR146Ars2910164CC genotype, HNF1αgene p. I27L TT genotype, and ACE I / D polymorphism DD genotype was significantly higher in women with GDM complicated with PE ( 178 180 ). Obesity is the main influencing factor of PE in women with GDM in this paper.…”
Section: Mechanism and Predictive Markersmentioning
confidence: 99%
“…Similar findings were described by Gomez et al, who found that the ACE Del/Del polymorphism was statistically higher in the severe COVID-19 group than in the mild disease group [ 6 ]. Furthermore, Dmitrenko et al found that the Del/Del genotypes were associated with increased risk of pregnancy complication in gestational diabetes mellitus women, increasing its risk by 2,96 [ 11 ]. Zmorzynski et al observed the association between Del/DEl genotype and more than 2-fold risk of multiple myeloma [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genotype and allele frequency of this polymorphism has been reported to be associated with several diseases including COVID-19 [ 10 ], cardiovascular disease [ 11 ], cancer [ 12 ], and diabetes mellitus and renal disease [ 13 ] in humans. In the present study, we aim to evaluate the association between ACE (Ins/Del) polymorphism and risk of tuberculosis in an admixture population such as the Brazilian population.…”
Section: Introductionmentioning
confidence: 99%
“…ACE gene I/D polymorphism is associated with increased PE risk in the general population. Dmitrenko et al postulated that this polymorphism also elevates the risk of PE in patients with GDM [ 160 ].…”
Section: Discussionmentioning
confidence: 99%